Employment protection, technology choice, and worker allocation - Eric J. Bartelsman; Pieter A. Gautier; Joris de Wind (Institute for the Study of Labor (IZA), 2010)
Using a country-industry panel dataset (EUKLEMS) we uncover a robust empirical regularity, namely that high-risk innovative sectors are relatively smaller in countries with strict employment protection legislation (EPL). To understand the mechanism, we develop a two-sector matching model where firms endogenously choose between a safe technology with known productivity and a risky technology with productivity subject to sizeable shocks. Strict EPL makes the risky technology relatively less attractive because it is more costly to shed workers upon receiving a low productivity draw. We calibrate the model using a variety of aggregate, industry and micro-level data sources. We then simulate the model to reflect both the observed differences across countries in EPL and the observed increase since the mid-1990s in the variance of firm performance associated with the adoption of information and communication technology. The simulations produce a differential response to the arrival of risky technology between low- and high-EPL countries that coincides with the findings in the data. The described mechanism can explain a considerable portion of the slowdown in productivity in the EU relative to the US since 1995.
Keywords: J65; O38; 330; Employment protection legislation; exit costs; information and communications technology; heterogeneous productivity; sectoral allocation; Arbeitnehmerschutz; Technologiewahl; Hochtechnologiesektor; Risiko; Mehr-Sektoren-Modell; Produktivität; Informationstechnik; Sektorale Beschäftigungsstruktur; Allokation; Vergleich; EU-Staaten; USA